2021
DOI: 10.1002/ehf2.13168
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of levosimendan, NO, and inhaled iloprost for pulmonary hypertension reversibility assessment in heart transplant candidates

Abstract: Aims Assessing reversibility of pulmonary vascular changes through vasoreactivity testing (VRT) optimizes end-stage heart failure patient selection for heart transplant. All efforts should be made to unload the left ventricle and reduce pulmonary vascular resistance to effectively exclude irreversible pulmonary hypertension. Methods and results We reviewed our centre's cardiac transplant registry database (2009-2017) for VRT and compared haemodynamic responses with 40 ppm inhaled NO (n = 14), 14-17 μg inhaled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Based on data from a retrospective review of a single-centre transplant list, Tavares-Silva and colleagues [ 95 ] deemed levosimendan to be a safe and effective alternative to either iloprost or nitric oxide for PH reversibility assessment of heart transplant candidates but emphasized that their data offered no insights into whether the use of levosimendan in this way facilitated better selection of transplant candidates or was associated with any robust indication of improved outcomes from transplantation. Levosimendan was the only drug of the three reviewed that reduced pulmonary artery wedge pressure and CVP.…”
Section: Pulmonary Hypertension and Right Ventricular Dysfunctionmentioning
confidence: 99%
“…Based on data from a retrospective review of a single-centre transplant list, Tavares-Silva and colleagues [ 95 ] deemed levosimendan to be a safe and effective alternative to either iloprost or nitric oxide for PH reversibility assessment of heart transplant candidates but emphasized that their data offered no insights into whether the use of levosimendan in this way facilitated better selection of transplant candidates or was associated with any robust indication of improved outcomes from transplantation. Levosimendan was the only drug of the three reviewed that reduced pulmonary artery wedge pressure and CVP.…”
Section: Pulmonary Hypertension and Right Ventricular Dysfunctionmentioning
confidence: 99%
“…Iloprost is a synthetic and relatively stable cyclin analogue with a relatively short duration of action, administered by inhalation 6-9 times a day. It has been demonstrated that the use of 100 μ g of iloprost in 6-9 inhalations per day for varying lengths of time, up to 1 year, in patients with different grades of PAH has been found to provide short- or long-term benefits [ 19 ]. Currently, the United States, Australia, and some other European countries have approved inhaled iloprost for direct use in the treatment of WHO cardiac class III or IV PAH, and in China, it was approved for the treatment of moderate PAH in 2006.…”
Section: Current Status Of Pah Treatment With Inhaled Formulationsmentioning
confidence: 99%
“…This mechanism is often demonstrated in invasive hemodynamic studies testing PVR reactivity among HT candidates. A positive response can be defined based on reduction of pulmonary pressure and PCWP with concomitant increase in CO ( 18 ). Nevertheless, changes in CO were not included in most previous studies evaluating LVAD therapy in elevated PVR patients ( 13 17 ).…”
Section: Discussionmentioning
confidence: 99%